2021
DOI: 10.3389/fnana.2021.748050
|View full text |Cite
|
Sign up to set email alerts
|

The Cortical Motor System in the Domestic Pig: Origin and Termination of the Corticospinal Tract and Cortico-Brainstem Projections

Abstract: The anatomy of the cortical motor system and its relationship to motor repertoire in artiodactyls is for the most part unknown. We studied the origin and termination of the corticospinal tract (CST) and cortico-brainstem projections in domestic pigs. Pyramidal neurons were retrogradely labeled by injecting aminostilbamidine in the spinal segment C1. After identifying the dual origin of the porcine CST in the primary motor cortex (M1) and premotor cortex (PM), the axons descending from those regions to the spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 113 publications
(181 reference statements)
0
8
0
Order By: Relevance
“…The neuroanatomical of corticospinal tract in the Yucatan pig remains poorly understood with some studies suggesting terminations at lower cervical or at T1 62 . Del Cerro showed numerous projections of CST from the primary motor cortex to T6 level in species of pig 63 . The exact anatomy in Yucatan pig remains unknown although our results suggest the presence of the corticospinal tract to levels lower than T6.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The neuroanatomical of corticospinal tract in the Yucatan pig remains poorly understood with some studies suggesting terminations at lower cervical or at T1 62 . Del Cerro showed numerous projections of CST from the primary motor cortex to T6 level in species of pig 63 . The exact anatomy in Yucatan pig remains unknown although our results suggest the presence of the corticospinal tract to levels lower than T6.…”
Section: Discussionmentioning
confidence: 65%
“…62 Del Cerro showed numerous projections of CST from the primary motor cortex to T6 level in species of pig. 63 The exact anatomy in Yucatan pig remains unknown although our results suggest the presence of the corticospinal tract to levels lower than T6. Small sample size is a major limitation of the study.…”
Section: Discussionmentioning
confidence: 73%
“…Thus, as previously demonstrated in rodents [ 3 , 24 , 25 ], the multimolecular complex of PLL/heparin/bFGF/fibronectin attached to the MFs was able to facilitate the growth of some axonal types in the porcine spinal cord, even in the inhibitory environment provided by the scarring cells. Neural tracers can be applied in swine [ 26 , 29 ] to study the origin and termination of spinal axonal tracts. However, in this preliminary work, only immunohistochemistry was used for axonal labeling, and no precise identification of the neuronal sources of regrowing axons was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, solid evidence of tissue repair with physiological and behavioral correlates of neural reconnection across the lesion should be demonstrated in large animal models of human neuropathology before advancing to human testing. In this regard, the use of swine in translational neuroscience is increasing because of its size, longevity, and developmental, physiological, and anatomical similarities [ 26 , 27 , 28 , 29 ] to humans. Biomaterials have been tested in pigs for reconstruction of different body organs [ 30 , 31 , 32 , 33 ], but their use in porcine spinal cord repair strategies is uncommon [ 4 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the human, this tract lies along the entire median fissure at spinal levels C1–C4, spreading to reach the most ventral surface of the cord (Jang & Kwon, 2013; Kwon et al, 2011). Tracing experiments in the pig [an animal model whose spinal cord organization is remarkably similar to that of the human (Leonard et al, 2017)] demonstrated that projections from the primary and pre‐motor cortex could be found up to spinal segment T6 (Del Cerro et al, 2021). In the humans, projections have been detected at around the upper thoracic levels; however, in isolated cases where the tract is particularly large, this has been seen as far down as the sacral segments (Nathan et al, 1990).…”
Section: General Description Of Human Spinal Cord Anatomymentioning
confidence: 99%